Experiencing good results promotes positive feelings to high-intensity exercise among young adults: A qualitative study - Høydal, Kjetil L.; Åsebø, Eli-Karin Sjåstad; Dahl, Silje Louise (Frontiers in Sports and Active Living, 2022)
Introduction From a public health perspective, it is important to gain more insight into how people can be motivated to maintain effective exercise routines. It is a common belief that moderate-intensity exercise is more pleasant and enjoyable than high-intensity training. This study aims to provide insight into 1) participants' expectations and preferences for training intensity prior to training, 2) how longer-term participation affect participants’ experience of endurance training with continuous moderate-intensity training and high-intensity interval training. Materials and methods A total of 22 participants (14 women and eight men) between the ages of 21–30 volunteered for participation. Participants were randomised and divided into two equal groups. A total of 17 participants, nine women and eight men, completed the study. One group did moderate-intensity longer-lasting training and the other did high-intensity interval training. All participant completed three training sessions per week for eight weeks. Semi-structured interviews were conducted with each participant before and after completing the training intervention. Data was analysed using thematic analysis. Results The results describe participants expectations prior to training, and how they experienced the actual training. The overall experience of training comprises several factors that work together. Both expectations and actual experiences (e.g., of physical pleasantness or unpleasantness, of positive or negative emotions, and of actual results from the training) contribute to the participants’ overall experience of exercise. Conclusion The major finding is that improved physical fitness was a stronger motivator than feelings of pleasantness. Experiencing good results seemed to downplay feelings of unpleasantness and reinforce positive feelings towards exercise. Lack of results reinforce negative feelings toward exercise. Participant reported high-intensity exercise as more unpleasant and exhaustive, but the ITG were more satisfied and experienced the training as more motivating.